Crime and weather: Evidence from the Czech Republic - Vojtěch Mišák (Charles University in Prague, Institute of Economic Studies (IES), 2022)
This article estimates the impact of weather on crime in the Czech Republic. Using detailed crime data during the years 2005-2015, I show that temperature has a significant positive effect on the total number of assaults, thefts, robberies and sexual crimes recorded. Furthermore, precipitation is found to have a negative significant effect on the number of assaults and sexual crimes committed. Finally, based on my results, temperature seems to cause an overall increase in assaults' and thefts' rates. Heat effect on sexual crimes is more a substitution effect between cold and hot days.
Keywords: K14; K42; K49; 330; crime; temperature; precipitation